2022
DOI: 10.3390/healthcare10061061
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Knee Osteochondral Fractures

Abstract: Osteochondral lesions (OCLs) that are frequently encountered in skeletally immature and adult patients are more common than once thought, and their incidence rate is rising. These lesions can appear in many synovial joints of the body, such as the shoulder, elbow, hip, and ankle, occurring most often in the knee. The term osteochondral lesion includes a vast spectrum of pathologies such as osteochondritis dissecans, osteochondral defects, osteochondral fractures, and osteonecrosis of the subchondral bone. When… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…These lesions may either be unstable OCD lesions, commonly seen in the pediatric population, or frank osteochondral fractures sustained after trauma, as in a direct blow to the knee by a helmet in football. 44,45 . In this technique, diagnostic arthroscopy is typically performed to evaluate the lesion.…”
Section: Osteochondral Fragment Internal Fixationmentioning
confidence: 99%
See 1 more Smart Citation
“…These lesions may either be unstable OCD lesions, commonly seen in the pediatric population, or frank osteochondral fractures sustained after trauma, as in a direct blow to the knee by a helmet in football. 44,45 . In this technique, diagnostic arthroscopy is typically performed to evaluate the lesion.…”
Section: Osteochondral Fragment Internal Fixationmentioning
confidence: 99%
“…In a select group of patients with unstable osteochondral fragments, fixation may be possible. These lesions may either be unstable OCD lesions, commonly seen in the pediatric population, or frank osteochondral fractures sustained after trauma, as in a direct blow to the knee by a helmet in football 44,45 …”
Section: Treatmentmentioning
confidence: 99%
“…They are also often associated with sprains and dislocations, frequently in the elbow, ankle, knee (femoral condyles and patella) and hip joints [11]. At the knee joint, anterior cruciate ligament (ACL) injuries account for less than 1% of cases; however, it was found that the incidence of OCFs might be as high as 80% in the case of ACL injuries [1,[11][12][13]. This is attributed to the valgus stress, which results in shearing forces that damage the cartilage of the femoral condyles [1].…”
Section: Introductionmentioning
confidence: 99%
“…They are also often associated with sprains and dislocations, frequently in the elbow, ankle, knee -femoral condyles and patella -and hip joints [11]. At the knee joint, anterior cruciate ligament (ACL) injuries account for less than 1% of cases, however, it was found that the incidence of OCFs might be as high as 80% in the case of ACL injuries [1,[11][12][13]. This is attributed to the valgus stress which results in shearing forces yielding damage to the cartilage of the femoral condyles [1,11].…”
Section: Introductionmentioning
confidence: 99%